Progressive Legal Approaches and the Prosecutorial Challenges in Executing the Indosurya Case - Sikotti, Dennis Fer (Jurnal Ilmu Hukum Kyadiren, 2025)
Asset recovery for victims in money laundering cases (Tindak Pidana Pencucian Uang/TPPU) poses a significant challenge within Indonesia’s criminal justice system, particularly in complex cases such as the Indosurya Savings and Loans Cooperative (KSP Indosurya). This study aims to evaluate the technical, legal, and institutional barriers encountered by executing prosecutors in implementing court decisions intended to restore victims’ financial losses. The research employs a normative legal approach, incorporating case studies and analyses of statutory regulations, judicial decisions, and execution documents. The findings reveal key obstacles, including discrepancies between court rulings and the factual conditions of the seized assets, the absence of explicit language such as “confiscated for the state” in verdicts, and weak inter-agency coordination. The study concludes that procedural reform and the adoption of a progressive legal approach are essential to ensure the effective enforcement of victim restitution. It recommends cross-sectoral synchronization and the reinforcement of the legal framework for asset execution as critical steps toward achieving substantive justice in money laundering cases.